A Novel Antimicrobial Peptide Scyreprocin From Mud Crab Scylla paramamosain Showing Potent Antifungal and Anti-biofilm Activity - Yang, Ying; Chen, Fangyi; Chen, Hui-Yun; Peng, Hui; Hao, Hua; Wang, Ke-Jian (Frontiers in Microbiology, 2020)
Natural antimicrobial peptides (AMPs) are potential antibiotic alternatives. Marine crustaceans are thought to generate more powerful and various potential AMPs to protect themselves from infections caused by pathogenic microorganisms in their complex aquatic habitat, thus becoming one of the most promising sources of AMPs or other bioactive substances. In the study, a novel protein was identified as an interacting partner of male-specific AMP SCY2 in Scylla paramamosain, and named scyreprocin. The recombinant product of scyreprocin was successfully expressed in Escherichia coli (rScyreprocin). Recombinant scyreprocin exerted potent, broad-spectrum antifungal, antibacterial and anti-biofilm activity (MICs from 0.5 to 32 μM), as well as rapid bactericidal (in 0.5 to 2 hours) and fungicidal (in 8 to 10 hours) kinetic via differential action modes including disruption of cell membrane integrity and induction of cell apoptosis. Besides its fungicidal activity against planktonic fungi, rScyreprocin prevented the adhesion of fungal cells, inhibited biofilm formation and eradicated the mature biofilms. Additionally, rScyreprocin showed profound inhibitory effect on spore germination of Aspergilus spp. (MICs from 4 to 8 μM). This peptide showed no cytotoxicity on murine and mammalian cells, and could improve the survival of Oryzias melastigma with the challenge of Vibrio harveyi. Taken together, the novel AMP scyreprocin would be a promising substitute for antibiotic to be used in aquaculture and medicine.